A nanoscale grinding process of natural quartz

CN122876252APending Publication Date: 2026-10-09HENAN JIELIDA SUPERHARD PROD CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611267026.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-20
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0004]然而,现有方式中通常直接在抛光机中加入大量研磨液,然后将水晶产品置于研磨液中进行研磨抛光操作,该研磨方式导致研磨作业中研磨液的耗费量较大,增大了水晶产品的加工成本,并且现有的研磨液研磨效果较差,循环使用寿命弱,严重影响了水晶产品的研磨效率以及研磨质量,有必要对其进行改进

Benefits of technology

[0013]与现有技术相比,本发明具有的优点和积极效果是:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a kind of natural crystal nanoscale grinding process, comprising the following steps: S1, the water crystal product after initial processing is rounded, and rounded product is obtained;S2, rounded product is placed in polishing machine, and primary grinding liquid is dropped into polishing machine, and primary polishing operation is carried out to rounded product by polishing machine;S3, the rounded product after primary polishing is ultrasonic cleaning operation;S4, repeat steps S2-S3, until the primary polishing and cleaning operation of rounded product is completed 2-3 times, and primary polishing product is obtained;S5, primary polishing product is placed again in polishing machine, and secondary grinding liquid is dropped, and secondary polishing operation is carried out to primary polishing product;S6, primary polishing product is ultrasonic cleaning operation;S7, repeat steps S5-S6, until the secondary polishing and cleaning operation of primary polishing product is completed 2-3 times, and water crystal finished product is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of crystal processing, and more particularly to a nanoscale grinding process for natural crystal. Background Technology

[0002] Quartz is a crystalline mineral, its main chemical component being silicon dioxide. In Western countries, anything transparent is considered quartz, so the term "quartz" includes colorless, transparent glass (K9 type, ordinary glass has a bluish tint) as well as natural quartz minerals. Well-developed single crystals are hexagonal pyramids, so they are usually found in massive or granular aggregates, generally colorless, gray, or milky white. When containing other mineral elements, they can appear purple, red, smoky, or brown. When pure, it forms colorless, transparent crystals. When containing trace elements such as aluminum and iron, it can appear pink, purple, yellow, or brown. Irradiation of trace elements can create different types of color centers, producing different colors such as purple, yellow, brown, and pink. Quartz containing accompanying mineral inclusions is called included quartz, such as rutilated quartz, green phantom quartz, and red rabbit hair quartz. The inclusions are often rutile, tourmaline, actinolite, mica, chlorite, etc.

[0003] During the processing of crystal, the surface of the crystal needs to be ground and polished to increase its transparency. This process is usually carried out in conjunction with a polishing machine and a polishing slurry. The polishing slurry is made by dispersing abrasive particles in a medium and is a polishing product with excellent chemical and mechanical properties. It can be used for grinding and polishing silicon wafers, compound crystals, precision optical devices, LCD panels, gemstones, metal workpieces, etc.

[0004] However, the existing method usually involves adding a large amount of polishing slurry directly to the polishing machine and then placing the crystal product in the slurry for polishing. This method results in a large consumption of polishing slurry during the polishing operation, which increases the processing cost of crystal products. Furthermore, the existing polishing slurry has poor polishing effect and short cycle life, which seriously affects the polishing efficiency and polishing quality of crystal products. It is necessary to improve it. Summary of the Invention

[0005] The purpose of this invention is to address the aforementioned problems by providing a simple, high-speed, and effective nanoscale grinding process for natural crystals. To achieve the above objectives, the technical solution of the present invention is as follows: A nanoscale grinding process for natural crystal includes the following steps: S1. Place the pre-processed crystal product in a grinding machine, add diamond powder, and perform a rounding operation to obtain a rounded product. S2. Place the rounded product in the polishing machine, set up a dripping system above the polishing machine to drip primary polishing liquid into the polishing machine at a fixed rate, and perform primary polishing operation on the rounded product through the polishing machine. S3. Place the rounded product after primary polishing into an ultrasonic cleaner, add cleaning agent and perform ultrasonic cleaning. S4. Repeat steps S2 to S3 until the rounded product has undergone 2 to 3 primary polishing and cleaning operations to obtain the primary polished product. S5. Place the primary polishing product back into the polishing machine, replace the primary polishing fluid with the secondary polishing fluid, and drip it into the polishing machine again at a fixed rate through the dripping system. Then, perform secondary polishing on the primary polishing product using the polishing machine. S6. Place the primary polished product in an ultrasonic cleaner, add cleaning agent, and perform ultrasonic cleaning. S7. Repeat steps S5 to S6 until the primary polished product has undergone 2 to 3 secondary polishing and cleaning operations to obtain the finished crystal product.

[0006] Furthermore, in step S1, the diamond abrasive is 430-450 mesh diamond abrasive.

[0007] Furthermore, in step S2, the polishing machine uses a polyurethane polishing pad with a porosity of 15-45%.

[0008] Furthermore, the dripping system is equipped with a heating rod to heat the primary or secondary grinding slurry placed in the dripping system to 60-75°C; the dripping system is equipped with a stirring device to uniformly stir the primary or secondary grinding slurry placed in the dripping system; the dripping rate of the primary or secondary grinding slurry is 60-240 drops / min.

[0009] Furthermore, in step S2, the primary grinding slurry is prepared by mixing silicon dioxide, cerium oxide, disodium ethylenediaminetetraacetate, polyhydroxy hyperbranched resin, cellulose nanofibers, and deionized water; the particle size of the silicon dioxide is 1-2 nm, and the particle size of the cerium oxide is 30-50 nm; the mass percentage of each component is: silicon dioxide 0.5-0.8%, cerium oxide 0.5-1.5%, disodium ethylenediaminetetraacetate 1-3%, polyhydroxy hyperbranched resin 4-7.5%, cellulose nanofibers 3.5-3.8%, and the balance is deionized water.

[0010] Furthermore, the cleaning agent is prepared by mixing hydroxyethylidene diphosphate, sodium ethylenediaminetetraacetate, octadecyl dihydroxyethylamine oxide, benzimidazole allyl sulfide, and water, with the following mass percentages for each component: 2-3% hydroxyethylidene diphosphate, 2-5% sodium ethylenediaminetetraacetate, 4.5-8% octadecyl dihydroxyethylamine oxide, 8-12% benzimidazole allyl sulfide, and the balance being water.

[0011] Furthermore, in step S5, the secondary grinding slurry is prepared by mixing silicon dioxide, cerium oxide, disodium ethylenediaminetetraacetate, polyhydroxy hyperbranched resin, cellulose nanofibers, and deionized water; the particle size of the silicon dioxide is 0.8-1.2 nm, and the particle size of the cerium oxide is 10-15 nm; the mass percentage of each component is as follows: silicon dioxide 0.9-1.9%, cerium oxide 0.8-3.5%, disodium ethylenediaminetetraacetate 2-3%, polyhydroxy hyperbranched resin 6-8.5%, cellulose nanofibers 3.5-3.8%, and the balance is deionized water.

[0012] Furthermore, the preparation steps of the primary and secondary polishing slurries are as follows: S11. Measure out silicon dioxide, cerium oxide, disodium ethylenediaminetetraacetate, polyhydroxy hyperbranched resin, cellulose nanofibers, and deionized water according to the component ratio. S12. Place deionized water in a container and heat it in a water bath to 35-45°C. Add disodium ethylenediaminetetraacetate and cellulose nanofibers in sequence under magnetic stirring. Keep the temperature constant and continue stirring at a speed of 150-250 r / min for 0.5-2 hours to obtain a mixed solution. S13. Mix silicon oxide and cerium oxide evenly and slowly add the mixture to the mixed solution. Heat rapidly to 70-85℃ and stir at 100-200 r / min for 0.5-1 hour. After stirring, let it cool naturally to room temperature. S14. Add cellulose nanofibers and polyhydroxy hyperbranched resin to the mixed solution, let stand for 5 to 8 hours, and then stir at 800 to 1200 r / min for 3 to 4 hours to obtain the primary or secondary grinding slurry.

[0013] Compared with the prior art, the advantages and positive effects of this invention are: This invention, when performing surface treatment on crystal products, first uses diamond abrasive to round the pre-processed crystal product, then uses a primary polishing slurry for primary polishing and cleaning, and finally uses a secondary polishing slurry for secondary polishing and cleaning, thereby achieving the desired surface treatment effect. During the polishing operation, the primary and secondary polishing slurries are added to the polishing machine at a fixed rate using a dripping system. This achieves the desired rounding polishing effect while avoiding excessive slurry addition that would waste slurry and increase processing costs. Furthermore, this invention uses nano-silica and nano-cerium oxide as the polishing matrix and designs a unique primary and secondary polishing slurry formula. This design results in better polishing effect and longer cycle life of the slurry, effectively improving the polishing efficiency and quality of crystal products, thus contributing significantly to the processing of crystal products. Detailed Implementation

[0014] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, any modifications, equivalent substitutions, improvements, etc., made by those skilled in the art to all other embodiments obtained without creative effort should be included within the protection scope of the present invention.

[0015] Example 1: This example discloses a nanoscale grinding process for natural crystal, including the following steps: S1. Place the pre-processed crystal product in a grinding machine, add 430-mesh diamond abrasive, and perform a rounding operation to obtain a rounded product. S2. Place the rounded product in a polishing machine. The polishing machine uses a polyurethane polishing pad with a porosity of 15%. A dripping system is set above the polishing machine. The dripping system contains a heating rod, which heats the primary polishing liquid in the dripping system to 60°C. The dripping system is also equipped with a stirring device, which uniformly stirs the primary polishing liquid in the dripping system. The dripping system drips the primary polishing liquid into the polishing machine at a dripping rate of 60 drops / min, and the polishing machine performs the primary polishing operation on the rounded product. The primary grinding slurry is made by mixing silicon dioxide, cerium oxide, disodium ethylenediaminetetraacetate, polyhydroxy hyperbranched resin, cellulose nanofibers, and deionized water; the maximum particle size of silicon dioxide is 1 nm, and the maximum particle size of cerium oxide is 30 nm; the mass percentage of each component is: silicon dioxide 0.5%, cerium oxide 0.5%, disodium ethylenediaminetetraacetate 1%, polyhydroxy hyperbranched resin 4%, cellulose nanofibers 3.5%, and the balance is deionized water.

[0016] S3. Place the rounded product after primary polishing into an ultrasonic cleaner, add cleaning agent and perform ultrasonic cleaning. The cleaning agent is made by mixing hydroxyethylidene diphosphate, sodium ethylenediaminetetraacetate, octadecyl dihydroxyethylamine oxide, benzimidazole allyl sulfide, and water. The mass percentages of each component are as follows: 2% hydroxyethylidene diphosphate, 2% sodium ethylenediaminetetraacetate, 4.5% octadecyl dihydroxyethylamine oxide, 8% benzimidazole allyl sulfide, and the balance is water.

[0017] S4. Repeat steps S2 to S3 until the rounded product has undergone two primary polishing and cleaning operations to obtain the primary polished product. S5. Place the primary polishing product back into the polishing machine, replace the primary polishing slurry with the secondary polishing slurry, heat the secondary polishing slurry in the dripping system to 60°C using the heating rod in the dripping system, and stir the secondary polishing slurry in the dripping system evenly using the stirring device; drip the secondary polishing slurry into the polishing machine at a dripping rate of 60 drops / min, and perform secondary polishing on the primary polishing product using the polishing machine; The secondary grinding fluid is made by mixing silicon dioxide, cerium oxide, disodium ethylenediaminetetraacetate, polyhydroxy hyperbranched resin, cellulose nanofibers, and deionized water; the maximum particle size of silicon dioxide is 0.8 nm, and the maximum particle size of cerium oxide is 10 nm; the mass percentage of each component is: silicon dioxide 0.9%, cerium oxide 0.8%, disodium ethylenediaminetetraacetate 2%, polyhydroxy hyperbranched resin 6%, cellulose nanofibers 3.5%, and the balance is deionized water.

[0018] S6. Place the primary polished product in an ultrasonic cleaner, add cleaning agent, and perform ultrasonic cleaning. S7. Repeat steps S5 to S6 until the primary polished product has undergone two secondary polishing and cleaning operations to obtain the finished crystal product.

[0019] The preparation steps for the primary and secondary polishing slurries are as follows: S11. Measure out silicon dioxide, cerium oxide, disodium ethylenediaminetetraacetate, polyhydroxy hyperbranched resin, cellulose nanofibers, and deionized water according to the component ratio. S12. Place deionized water in a container and heat it in a water bath to 35°C. Add disodium ethylenediaminetetraacetate and cellulose nanofibers in sequence under magnetic stirring. Keep the temperature constant and continue stirring at 150 r / min for 0.5 hours to obtain a mixed solution. S13. Mix silicon oxide and cerium oxide evenly and slowly add the mixture to the mixed solution. Heat the mixture to 70°C and stir at 100 r / min for 0.5 hours. After stirring, let it cool naturally to room temperature. S14. Add cellulose nanofibers and polyhydroxy hyperbranched resin to the mixed solution, let stand for 5 hours, and then stir at 800 r / min for 3 hours to obtain the primary or secondary grinding slurry.

[0020] Example 2: This example discloses a nanoscale grinding process for natural crystal, including the following steps: S1. Place the pre-processed crystal product in a grinding machine, add 440-mesh diamond abrasive, and perform a rounding operation to obtain a rounded product. S2. Place the rounded product in a polishing machine. The polishing machine uses a polyurethane polishing pad with a porosity of 30%. A dripping system is set above the polishing machine. The dripping system contains a heating rod, which heats the primary polishing liquid in the dripping system to 70°C. The dripping system is equipped with a stirring device, which uniformly stirs the primary polishing liquid in the dripping system. The dripping system drips the primary polishing liquid into the polishing machine at a dripping rate of 100 drops / min, and the polishing machine performs the primary polishing operation on the rounded product. The primary grinding slurry is made by mixing silicon dioxide, cerium oxide, disodium ethylenediaminetetraacetate, polyhydroxy hyperbranched resin, cellulose nanofibers, and deionized water; the maximum particle size of silicon dioxide is 2 nm, and the maximum particle size of cerium oxide is 40 nm; the mass percentage of each component is: silicon dioxide 0.6%, cerium oxide 1%, disodium ethylenediaminetetraacetate 2%, polyhydroxy hyperbranched resin 6%, cellulose nanofibers 3.6%, and the balance is deionized water.

[0021] S3. Place the rounded product after primary polishing into an ultrasonic cleaner, add cleaning agent and perform ultrasonic cleaning. The cleaning agent is made by mixing hydroxyethylidene diphosphate, sodium ethylenediaminetetraacetate, octadecyl dihydroxyethylamine oxide, benzimidazole allyl sulfide, and water. The mass percentage of each component is as follows: 3% hydroxyethylidene diphosphate, 3% sodium ethylenediaminetetraacetate, 6% octadecyl dihydroxyethylamine oxide, 10% benzimidazole allyl sulfide, and the balance is water.

[0022] S4. Repeat steps S2 to S3 until the rounded product has undergone three primary polishing and cleaning operations to obtain the primary polished product. S5. Place the primary polishing product back into the polishing machine, replace the primary polishing slurry with the secondary polishing slurry, heat the secondary polishing slurry in the dripping system to 70°C using the heating rod in the dripping system, and stir the secondary polishing slurry in the dripping system evenly using the stirring device; drip the secondary polishing slurry into the polishing machine at a dripping rate of 120 drops / min, and perform secondary polishing on the primary polishing product using the polishing machine; The secondary grinding fluid is made by mixing silicon dioxide, cerium oxide, disodium ethylenediaminetetraacetate, polyhydroxy hyperbranched resin, cellulose nanofibers, and deionized water; the maximum particle size of silicon dioxide is 1 nm, and the maximum particle size of cerium oxide is 12 nm; the mass percentage of each component is: silicon dioxide 1.5%, cerium oxide 2%, disodium ethylenediaminetetraacetate 2%, polyhydroxy hyperbranched resin 7%, cellulose nanofibers 3.7%, and the balance is deionized water.

[0023] S6. Place the primary polished product in an ultrasonic cleaner, add cleaning agent, and perform ultrasonic cleaning. S7. Repeat steps S5 to S6 until the primary polished product has undergone three secondary polishing and cleaning operations to obtain the finished crystal product.

[0024] The preparation steps for the primary and secondary polishing slurries are as follows: S11. Measure out silicon dioxide, cerium oxide, disodium ethylenediaminetetraacetate, polyhydroxy hyperbranched resin, cellulose nanofibers, and deionized water according to the component ratio. S12. Place deionized water in a container and heat it in a water bath to 40°C. Add disodium ethylenediaminetetraacetate and cellulose nanofibers in sequence under magnetic stirring. Keep the temperature constant and continue stirring at 200 r / min for 1 hour to obtain a mixed solution. S13. Mix silicon oxide and cerium oxide evenly and slowly add the mixture to the mixed solution. Heat rapidly to 80°C and stir at 150 r / min for 0.8 hours. After stirring, let it cool naturally to room temperature. S14. Add cellulose nanofibers and polyhydroxy hyperbranched resin to the mixed solution, let stand for 6 hours, and then stir at 1000 r / min for 3 hours to obtain the primary or secondary grinding slurry.

[0025] Example 3: This example discloses a nanoscale grinding process for natural crystal, including the following steps: S1. Place the pre-processed crystal product in a grinding machine, add 450-mesh diamond abrasive, and perform a rounding operation to obtain a rounded product. S2. Place the rounded product in a polishing machine. The polishing machine uses a polyurethane polishing pad with a porosity of 45%. A dripping system is set above the polishing machine. The dripping system contains a heating rod, which heats the primary polishing liquid in the dripping system to 75°C. The dripping system is equipped with a stirring device, which uniformly stirs the primary polishing liquid in the dripping system. The dripping system drips the primary polishing liquid into the polishing machine at a dripping rate of 240 drops / min, and the polishing machine performs the primary polishing operation on the rounded product. The primary grinding slurry is made by mixing silicon dioxide, cerium oxide, disodium ethylenediaminetetraacetate, polyhydroxy hyperbranched resin, cellulose nanofibers, and deionized water; the maximum particle size of silicon dioxide is 2 nm, and the maximum particle size of cerium oxide is 50 nm; the mass percentage of each component is: silicon dioxide 0.8%, cerium oxide 1.5%, disodium ethylenediaminetetraacetate 3%, polyhydroxy hyperbranched resin 7.5%, cellulose nanofibers 3.8%, and the balance is deionized water.

[0026] S3. Place the rounded product after primary polishing into an ultrasonic cleaner, add cleaning agent and perform ultrasonic cleaning. The cleaning agent is made by mixing hydroxyethylidene diphosphate, sodium ethylenediaminetetraacetate, octadecyl dihydroxyethylamine oxide, benzimidazole allyl sulfide, and water. The mass percentage of each component is as follows: 3% hydroxyethylidene diphosphate, 5% sodium ethylenediaminetetraacetate, 8% octadecyl dihydroxyethylamine oxide, 12% benzimidazole allyl sulfide, and the balance is water.

[0027] S4. Repeat steps S2 to S3 until the rounded product has undergone three primary polishing and cleaning operations to obtain the primary polished product. S5. Place the primary polishing product back into the polishing machine, replace the primary polishing slurry with the secondary polishing slurry, heat the secondary polishing slurry in the dripping system to 75°C using the heating rod in the dripping system, and stir the secondary polishing slurry in the dripping system evenly using the stirring device; drip the secondary polishing slurry into the polishing machine at a dripping rate of 240 drops / min, and perform secondary polishing on the primary polishing product using the polishing machine; The secondary grinding fluid is made by mixing silicon dioxide, cerium oxide, disodium ethylenediaminetetraacetate, polyhydroxy hyperbranched resin, cellulose nanofibers, and deionized water; the maximum particle size of silicon dioxide is 1.2 nm, and the maximum particle size of cerium oxide is 15 nm; the mass percentage of each component is: silicon dioxide 1.9%, cerium oxide 3.5%, disodium ethylenediaminetetraacetate 3%, polyhydroxy hyperbranched resin 8.5%, cellulose nanofibers 3.8%, and the balance is deionized water.

[0028] S6. Place the primary polished product in an ultrasonic cleaner, add cleaning agent, and perform ultrasonic cleaning. S7. Repeat steps S5 to S6 until the primary polished product has undergone three secondary polishing and cleaning operations to obtain the finished crystal product.

[0029] The preparation steps for the primary and secondary polishing slurries are as follows: S11. Measure out silicon dioxide, cerium oxide, disodium ethylenediaminetetraacetate, polyhydroxy hyperbranched resin, cellulose nanofibers, and deionized water according to the component ratio. S12. Place deionized water in a container and heat it in a water bath to 45°C. Add disodium ethylenediaminetetraacetate and cellulose nanofibers in sequence under magnetic stirring. Keep the temperature constant and continue stirring at 250 r / min for 2 hours to obtain a mixed solution. S13. Mix silicon oxide and cerium oxide evenly and slowly add them to the mixed solution. Heat the mixture to 85°C and stir at 200 r / min for 1 hour. After stirring, let it cool naturally to room temperature. S14. Add cellulose nanofibers and polyhydroxy hyperbranched resin to the mixed solution, let stand for 8 hours, and then stir at 1200 r / min for 4 hours to obtain the primary or secondary grinding slurry.

[0030] To verify the effectiveness of the technical solution of this invention, three comparative experiments were designed. These experiments used existing technologies and the technical solution of this invention to perform surface treatment operations on pre-processed crystal products of the same particle size. The experimental results are shown in the table below:

[0031] As can be seen from the table above, compared with the existing technical solutions, the technical solution of this invention can significantly reduce the amount of polishing liquid used for surface treatment of crystal products, while improving the surface treatment efficiency of crystal products, and the polishing quality is not affected in any way, thus having broad market promotion value.

[0032] This invention, when performing surface treatment on crystal products, first uses diamond abrasive to round the pre-processed crystal product, then uses a primary polishing slurry for primary polishing and cleaning, and finally uses a secondary polishing slurry for secondary polishing and cleaning, thereby achieving the desired surface treatment effect. During the polishing operation, the primary and secondary polishing slurries are added to the polishing machine at a fixed rate using a dripping system. This achieves the desired rounding polishing effect while avoiding excessive slurry addition that would waste slurry and increase processing costs. Furthermore, this invention uses nano-silica and nano-cerium oxide as the polishing matrix and designs a unique primary and secondary polishing slurry formula. This design results in better polishing effect and longer cycle life of the slurry, effectively improving the polishing efficiency and quality of crystal products, thus contributing significantly to the processing of crystal products.

Claims

1. A nanoscale grinding process for natural crystal, characterized in that: Includes the following steps: S1. Place the pre-processed crystal product in a grinding machine, add diamond powder and perform a rounding operation to obtain a rounded product. S2. Place the rounded product in the polishing machine, set up a dripping system above the polishing machine to drip primary polishing liquid into the polishing machine at a fixed rate, and perform primary polishing operation on the rounded product through the polishing machine. S3. Place the rounded product after primary polishing into an ultrasonic cleaner, add cleaning agent and perform ultrasonic cleaning. S4. Repeat steps S2 to S3 until the rounded product has undergone 2 to 3 primary polishing and cleaning operations to obtain the primary polished product. S5. Place the primary polishing product back into the polishing machine, replace the primary polishing fluid with the secondary polishing fluid, and drip it into the polishing machine again at a fixed rate through the dripping system. Then, perform secondary polishing on the primary polishing product using the polishing machine. S6. Place the primary polished product in an ultrasonic cleaner, add cleaning agent, and perform ultrasonic cleaning. S7. Repeat steps S5 to S6 until the primary polished product has undergone 2 to 3 secondary polishing and cleaning operations to obtain the finished crystal product.

2. The nanoscale grinding process for natural crystal as described in claim 1, characterized in that: In step S1, the corundum is 430-450 mesh corundum.

3. The nanoscale grinding process for natural crystal as described in claim 1, characterized in that: In step S2, the polishing machine uses a polyurethane polishing pad with a porosity of 15-45%.

4. The nano-grinding process for natural crystal as described in claim 3, characterized in that: The dripping system is equipped with a heating rod, which heats the primary or secondary grinding slurry placed in the system to 60-75°C. The dripping system is also equipped with a stirring device, which performs uniform stirring of the primary or secondary grinding slurry placed in the system. The dripping rate of the primary or secondary grinding slurry is 60-240 drops / min.

5. The nanoscale grinding process for natural crystal as described in claim 4, characterized in that: In step S2, the primary grinding slurry is prepared by mixing silicon dioxide, cerium oxide, disodium ethylenediaminetetraacetate, polyhydroxy hyperbranched resin, cellulose nanofibers, and deionized water; the particle size of silicon dioxide is 1-2 nm, and the particle size of cerium oxide is 30-50 nm; the mass percentage of each component is: silicon dioxide 0.5-0.8%, cerium oxide 0.5-1.5%, disodium ethylenediaminetetraacetate 1-3%, polyhydroxy hyperbranched resin 4-7.5%, cellulose nanofibers 3.5-3.8%, and the balance is deionized water.

6. The nanoscale grinding process for natural crystal as described in claim 5, characterized in that: The cleaning agent is made by mixing hydroxyethylidene diphosphate, sodium ethylenediaminetetraacetate, octadecyl dihydroxyethylamine oxide, benzimidazole allyl sulfide, and water. The mass percentages of each component are as follows: 2-3% hydroxyethylidene diphosphate, 2-5% sodium ethylenediaminetetraacetate, 4.5-8% octadecyl dihydroxyethylamine oxide, 8-12% benzimidazole allyl sulfide, and the balance being water.

7. The nanoscale grinding process for natural crystal as described in claim 6, characterized in that: In step S5, the secondary grinding slurry is prepared by mixing silicon dioxide, cerium oxide, disodium ethylenediaminetetraacetate, polyhydroxy hyperbranched resin, cellulose nanofibers, and deionized water; the particle size of silicon dioxide is 0.8-1.2 nm, and the particle size of cerium oxide is 10-15 nm; the mass percentage of each component is as follows: silicon dioxide 0.9-1.9%, cerium oxide 0.8-3.5%, disodium ethylenediaminetetraacetate 2-3%, polyhydroxy hyperbranched resin 6-8.5%, cellulose nanofibers 3.5-3.8%, and the balance is deionized water.

8. The nanoscale grinding process for natural crystal as described in claim 7, characterized in that: The preparation steps for the primary and secondary polishing slurries are as follows: S11. Measure out silicon dioxide, cerium oxide, disodium ethylenediaminetetraacetate, polyhydroxy hyperbranched resin, cellulose nanofibers, and deionized water according to the component ratio. S12. Place deionized water in a container and heat it in a water bath to 35-45°C. Add disodium ethylenediaminetetraacetate and cellulose nanofibers in sequence under magnetic stirring. Keep the temperature constant and continue stirring at a speed of 150-250 r / min for 0.5-2 hours to obtain a mixed solution. S13. Mix silicon oxide and cerium oxide evenly and slowly add the mixture to the mixed solution. Heat rapidly to 70-85℃ and stir at 100-200 r / min for 0.5-1 hour. After stirring, let it cool naturally to room temperature. S14. Add cellulose nanofibers and polyhydroxy hyperbranched resin to the mixed solution, let stand for 5 to 8 hours, and then stir at 800 to 1200 r / min for 3 to 4 hours to obtain the primary or secondary grinding slurry.